It's about time: Implications of the period length in an equilibrium job search model - Ronald P. Wolthoff (Institute for the Study of Labor (IZA), 2011)
This paper analyzes the role of the period length in a search model of the labor market and argues that it has profound implications for the market equilibrium. In the model, job offers and job destruction shocks arrive according to a Poisson process in continuous time, but institutional factors and/or informational frictions may delay workers' transitions into or out of a job. This effectively creates discrete time periods of arbitrary length, with continuous time being the limit case when the period length goes to zero. Longer periods introduce the possibility of simultaneity or recall of job offers, affecting the labor share, the amount of wage dispersion, as well as the allocation of workers over jobs with different productivity levels. Misspecification of the period length may therefore lead to inconsistent estimates of structural parameters and wrong conclusions on optimal policy.
urn:nbn:de:101:1-201110263408
Keywords: J64; J31; D83; 330; simultaneous search; on-the-job search; wage dispersion; labor market frictions; Arbeitsuche; Arbeitsmobilität; Dauer; Lohnstruktur; Arbeitsmarkttheorie; Unvollkommener Markt; Gleichgewicht; Theorie